Determination of arm and leg contribution to propulsion and percentage of coordination in butterfly swimming - Shahbazi-Moghaddam, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The Indirect Measurement of Active Drag (IMAD) was used to study the contribution of the legs and arms to propulsion in butterfly swimming. Contrary to MAD (Measuring of Active Drag) system, the IMAD can be used for all strokes and therefore enabled us to study the butterfly swim to estimate not only the percentage of leg and arm contribution to propulsion but also the percentage of swimmers` arms and legs co- ordinations. The method revealed that the best coordination was 78.% and that the contribution of arms and legs in propulsive force were 92% and 66% and in velocities were 98% and 88% respectively, showing that the swimmers received arm contribution better than leg contribution in propelling and velocity.